1999
DOI: 10.1017/s0950268899003015
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal protozoa in HIV-infected patients in Apulia, South Italy

Abstract: Protozoa are important enteric pathogens in patients with human immunodeficiency virus (HIV) infection. In this study the prevalence of intestinal protozoa in 154 HIV-infected patients, with or without diarrhoea, in our region (Apulia, South Italy) was evaluated between December 1993 and February 1998. In the majority of patients CD4+ T cell count was below 200/microl. The overall prevalence of intestinal protozoa was 43/154 (27.92%). Twenty-eight (43.08%) out of 65 patients with diarrhoea and 15 (16-85%) out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
26
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 38 publications
3
26
0
1
Order By: Relevance
“…However, the difference was not observed to be statistically significant (p = 0.14). This finding is similar to other studies performed elsewhere [7,26,28]. This could be explained in that females are the ones more engaged with domestic chores and farming which exposes them to intestinal parasites.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the difference was not observed to be statistically significant (p = 0.14). This finding is similar to other studies performed elsewhere [7,26,28]. This could be explained in that females are the ones more engaged with domestic chores and farming which exposes them to intestinal parasites.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, intestinal parasites were isolated using the formol ether concentration and the kato-katz techniques in addition to methods involving staining with the modified field stain and the modified Ziehl-Neelsen stain meanwhile the other studies performed elsewhere at best involved the use of only one concentration and one staining technique. The prevalence of intestinal parasites was also high compared to that reported in other countries, 27.9% in Apulia, Italy [26] and the 28.1% and 42.9% observed in Abuja and Abeokuta respectively in Nigeria [27]. However, the prevalence observed in this study was similar to the 81.8% reported in Tanzania [28] and the 79.3% in Osun state of Nigeria [29].…”
Section: Discussionsupporting
confidence: 73%
“…Diarrhea was common and strongly associated in patients with low CD4 cell count. This finding is in agreement with similar studies [30][31][32]. In addition, HIV patients may be prone to oxidative stress that may contribute to the process of diarrhea and a study conducted in Tunisia among the general population has shown that the oxidative stress is associated with gastrointestinal disturbances including diarrhea [33].…”
Section: Discussionsupporting
confidence: 92%
“…Respectively, the most common infectious agents of the chronic diarrhea, regardless of the number of CD4 cells, are: Clostridium diffi cile, Giardia lamblia, Entamoeba histolytica. In patients with a CD4 cells <100/mm3, the most common infectious agents of chronic diarrhea are: Microsporidia, Cryptosporidium spp., Mycobacterium avium complex, Isospora beli, Cyclospora cayetanensis, Cytomegalovirus (CMV) (especially in cases with CD4 cells < 50/mm3) [1,5,6,13].…”
mentioning
confidence: 99%
“…For patients with CD4 cell count between 100-200/mm3, it is enough to perform fl exible sigmoidoscopy and biopsy, because CMV infection is less likely to occur at higher CD4 count [7,9]. To establish intestinal protozoa is necessary to examine the stools with specifi c staining methods: Ziehl-Neelsen, Giemsa, Heidenhain, Masson [1,5,6,8]. If the result is negative, it is also recommended colonoscopy with intestinal biopsy and electron microscopy, and molecular techniques to demonstrate the antigen in feces.…”
mentioning
confidence: 99%